Complete mitochondrial genomes of eleven extinct or possibly extinct bird species. (11th October 2016) - Anmarkrud, Jarl A.; Lifjeld, Jan T.
Abstract: Natural history museum collections represent a vast source of ancient and historical DNA samples from extinct taxa that can be utilized by high‐throughput sequencing tools to reveal novel genetic and phylogenetic information about them. Here, we report on the successful sequencing of complete mitochondrial genome sequences (mitogenomes) from eleven extinct bird species, using de novo assembly of short sequences derived from toepad samples of degraded DNA from museum specimens. For two species (the Passenger Pigeon Ectopistes migratorius and the South Island Piopio Turnagra capensis ), whole mitogenomes were already available from recent studies, whereas for five others (the Great Auk Pinguinis impennis, the Imperial Woodpecker Campehilus imperialis, the Huia Heteralocha acutirostris, the Kauai Oo Moho braccathus and the South Island Kokako Callaeas cinereus ), there were partial mitochondrial sequences available for comparison. For all seven species, we found sequence similarities of >98%. For the remaining four species (the Kamao Myadestes myadestinus, the Paradise Parrot Psephotellus pulcherrimus, the Ou Psittirostra psittacea and the Lesser Akialoa Akialoa obscura ), there was no sequence information available for comparison, so we conducted blast searches and phylogenetic analyses to determine their phylogenetic positions and identify their closest extant relatives. These mitogenomes will be valuable for future analyses of avian phylogenetics and illustrate the importance of museum collections as repositories for genomics resources.